2022
DOI: 10.1002/joc.7651
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal forecasting of tropical cyclones over the Bay of Bengal using a hybrid statistical/dynamical model

Abstract: The post-monsoon (October-November-December) tropical cyclone (TC) over the Bay of Bengal is one of the most devastating natural disasters causing economic and human losses over India and its neighbouring countries. This study discusses a hybrid statistical/dynamical model developed to forecast the postmonsoon cyclone activities over the Bay of Bengal, where 80% of the TCs of the North Indian Ocean are originated. In the hybrid model, the coupled model CFSv2 predicts the large-scale climate indices, and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…When two events occur at the same date, we consider only the closest to the BMD network using the spatial average across the 34 stations. The categories for the available 6,679 three‐hourly time steps between 1998 and 2019 are almost always (except two cases categorized as “low” and one case not categorized) at least “depression.” We merge the categories “depression” (maximum sustained wind 17–27 knots, i.e., 31–49 km·h −1 ) and “deep depression” (maximum sustained wind 28–33 knots, i.e., 50–61 km·h −1 ) into a single “depression” category and all other “cyclonic storms” (maximum sustained wind ≥34 knots, i.e., ≥ 62 km·h −1 ) categories as a single “cyclone” category (Sabeerali et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…When two events occur at the same date, we consider only the closest to the BMD network using the spatial average across the 34 stations. The categories for the available 6,679 three‐hourly time steps between 1998 and 2019 are almost always (except two cases categorized as “low” and one case not categorized) at least “depression.” We merge the categories “depression” (maximum sustained wind 17–27 knots, i.e., 31–49 km·h −1 ) and “deep depression” (maximum sustained wind 28–33 knots, i.e., 50–61 km·h −1 ) into a single “depression” category and all other “cyclonic storms” (maximum sustained wind ≥34 knots, i.e., ≥ 62 km·h −1 ) categories as a single “cyclone” category (Sabeerali et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal forecasts of diverse hydroclimatic variables such as precipitation, evaporation, sea water level, sea level pressure or large-scale climate indices have also been used to drive ML models of precipitation (Madadgar et al, 2016), streamflow, and tropical cyclone activity (Sabeerali et al, 2022). For instance, atmosphere-ocean teleconnections obtained from the Initialization times are 0.5, 5.5 and 9.5 months ahead of the summer season.…”
Section: Sub-seasonal To Decadal Hybrid Forecastsmentioning
confidence: 99%
“…A study over the Netherlands using streamflow, precipitation, and evaporation found that the hybrid ML approach outperformed climatological reference forecasts by approximately 60% and 80% for streamflow and surface water level, respectively, using various machine learning models (Hauswirth et al, 2022). Another study employed predictions of large-scale indices by the CFSv2 model to predict the frequency of tropical cyclones in the Bay of Bengal using principal component regression (Sabeerali et al, 2022).…”
Section: Sub-seasonal To Decadal Hybrid Forecastsmentioning
confidence: 99%
“…With the exception of few papers (Nath et al, 2015(Nath et al, , 2016Sabeerali et al, 2022), the majority of preceding studies have successfully documented the concurrent association between a number of large-scale meteorological factors and TC activity with limited work being put into developing the prediction models. For the mitigation and prevention of disasters, reliable seasonal forecasting is essential for predicting the number of seasonal TCs in NIO.…”
Section: Introductionmentioning
confidence: 99%
“…The forecast skill for MLP, GRNN and RBF‐based ANN models were found to be 0.82, 0.79 and 0.80, respectively. In a recent work, Sabeerali et al, 2022 developed a hybrid statistical/dynamical model for estimating seasonal TC frequency in BoB using CFSv2 model, with a 2‐month lead time.…”
Section: Introductionmentioning
confidence: 99%